2022
DOI: 10.3390/cells11030495
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women and Endocrine Disruptors: Role of P2X7 Receptor and Mitochondrial Alterations in Placental Cell Disorders

Abstract: In pregnant women, the lungs, skin and placenta are exposed daily to endocrine-disrupting chemicals (EDCs). EDCs induce multiple adverse effects, not only on endocrine organs, but also on non-endocrine organs, with the P2X7 cell death receptor being potentially the common key element. Our objective was first to investigate mechanisms of EDCs toxicity in both endocrine and non-endocrine cells through P2X7 receptor activation, and second, to compare the level of activation in lung, skin and placental cells. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…The uterus is not an endocrine organ; it can respond to hormones but cannot secrete any of them. All these observations lead to the hypothesis that EDCs act differently depending on the tissue (uterus, mammary gland and placenta), which is in accordance to our previous results obtained in lung, skin and placental cells [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The uterus is not an endocrine organ; it can respond to hormones but cannot secrete any of them. All these observations lead to the hypothesis that EDCs act differently depending on the tissue (uterus, mammary gland and placenta), which is in accordance to our previous results obtained in lung, skin and placental cells [20].…”
Section: Discussionsupporting
confidence: 91%
“…The hPlacentox assay, selected by the public–private PEPPER platform for the pre-validation of methods for endocrine disruptors characterization, is based on the human placental JEG-Tox cell model and allows the study of not only hormones disruption (both steroids and polypeptides), but also adverse health effects in the same cells [ 17 ], to meet WHO’s definition of EDCs [ 18 ]. Our previous studies in JEG-Tox cells showed that P2X7 receptor activation would be a common cellular mechanism of toxicity for EDCs in placenta [ 19 , 20 ]. P2X7 receptor activation is reported to be involved in multiple pathologies from immune disorders to degenerative diseases and placental disorders [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To perform our study, we selected a human placental model, the JEG-3 cells, as we previously demonstrated that JEG-Tox cells can be of great value in placental toxicology studies [ 28 ]. We demonstrated in our previous work in these cells that the activation of the P2X7 receptor is a marker of placental toxicity including endocrine-disrupting chemical-induced toxicity, as we highlighted that the well-known endocrine-disrupting chemicals known as bisphenol A or diethylstilbestrol, despite their chemical differences, shared a common mechanism: the activation of the P2X7 degenerative receptor in human placental cells [ 25 , 26 , 27 ]. Our results showed an activation of the P2X7 degenerative receptor induced by non-cytotoxic concentrations of forskolin from 1µM, demonstrating a placental toxicity of forskolin.…”
Section: Discussionmentioning
confidence: 99%
“…The choriocarcinoma-derived JEG-3 cell-line (ATCC HTB-36, Manassas, VA, USA), was selected based on the results of previous studies highlighting the use of these endocrine cells for placental toxicity studies [ 25 , 26 , 27 , 28 ]. JEG-3 cells were cultured in Minimum Essential Medium Eagle’s medium supplemented with 10% FBS, 2 mM of glutamine, 50 U/mL of penicillin and 50 µg/mL of streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation